CHARACTERISTICS OF MOTHERS AND STUNTING TODDLERS IN PEKUNCEN VILLAGE, WIRADESA, PEKALONGAN, INDONESIA - Siti Rofiqoh; Imam Hanifudin Rizkian; Naila Vandawi; Febri Lianasari (Epidemiology and Society Health Review (ESHR), 2020)
Background: Stunting is the condition of short stature due to abnormal growth caused by a severe malnutrition problem that needs attention. Stunting can cause health problems, decrease productivity, and trigger poverty in the future. This study aims to determine the characteristics of mothers and stunting toddlers in Pekuncen village Wiradesa Pekalongan District, Central Java, Indonesia.Methods: The study was conducted in Pekuncen village in the Wiradesa subdistrict of the Pekalongan District. The retrospective design was used in this study. Respondent was recruited using total sampling techniques. A set of questionnaires was employed to collect the data among 35 respondents, which is the mothers of stunting toddler.Results: The results showed most of the respondents (82.7%) hold basic education level. 77.1% of respondents have family income < regional minimum salary of Pekalongan District. More than half of respondents (68.6%) have less nutrition knowledge. No mothers have good nutrition knowledge. Less than half (42.9%) provide parenting democratic type of feeding, and there are still 14.3% of mothers giving the neglect parenting feeding type. While the characteristics of stunting toddlers are 68.6% female, 37.1% aged 3-4 years, 28.6% aged 1-3 years, 42.9% do not get exclusive breastfeeding, and 88.6% have a history of normal born weight.Conclusions: Stunting toddler in Pekuncen village Wiradesa, Pekalongan was associated with a parent who has elementary education, family income less than the Regional Minimum Salary. Most of them have less nutrition knowledge level, and almost half of them provide parenting with the democratic type of feeding. While the characteristics of stunting toddlers were the majority of women, and nearly half do not get exclusive breastfeeding, and most have a normal birth weight history. We suggest that related parties should collaborate to reduce stunting prevalence based on the characteristics of mothers and stunting toddlers.Â